Molecular mechanisms and therapeutic potential of natural flavonoids in diabetic nephropathy: Modulation of intracellular developmental signaling pathways - Mahaboob Khan Sulaiman (Elsevier, 2024)
Recognized as a common microvascular complication of diabetes mellitus (DM), diabetic nephropathy (DN) is the principal cause of chronic end-stage renal disease (ESRD). Patients with diabetes have an approximately 25% risk of developing progressive renal disease. The underlying principles of DN control targets the dual outcomes of blood glucose regulation through sodium glucose cotransporter 2 (SGLT 2) blockade and hypertension management through renin-angiotensin-aldosterone inhibition. However, these treatments are ineffective in halting disease progression to kidney failure and cardiovascular comorbidities. Recently, the dysregulation of subcellular signaling pathways has been increasingly implicated in DN pathogenesis. Natural compounds are emerging as effective and side-effect-free therapeutic agents that target intracellular pathways. This narrative review synthesizes recent insights into the dysregulation of maintenance pathways in DN, drawing from animal and human studies. To compile this review, articles reporting DN signaling pathways and their treatment with natural flavonoids were collected from PubMed, Cochrane Library Web of Science, Google Scholar and EMBASE databases since 2000. As therapeutic interventions are frequently based on the results of clinical trials, a brief analysis of data from current phase II and III clinical trials on DN is discussed.